Oral Chemotherapy for Treatment of Lung Cancer - Jonna, Sushma; Reuss, Joshua E.; Kim, Chul; Liu, Stephen V. (Frontiers in Oncology, 2020)
The global COVID-19 pandemic has disrupted healthcare delivery, particularly for patients with advanced lung cancer. While certain aspects of care can be safely omitted or delayed, systemic therapy plays an important role in survival and quality of life for patients with advanced lung cancer; limiting access to systemic therapy will compromise cancer-related outcomes. This can be at odds with strategies to mitigate risk of COVID-19 exposure, which include reducing hospital and clinic visits. One important strategy is implementation of oral cancer therapies. Many standard regimens require intravenous infusions but there are specific circumstances where an oral agent could be an acceptable alternative. Integrating oral therapeutics can permit patients to receive effective systemic treatment without the exposure risks associated with frequent infusions. Here, we review currently available oral cytotoxic agents with a potential role in the treatment of lung cancer.